2021
DOI: 10.1093/sleep/zsab276
|View full text |Cite
|
Sign up to set email alerts
|

Association of magnesium intake with sleep duration and sleep quality: findings from the CARDIA study

Abstract: Study Objectives As an antagonist of calcium (Ca), magnesium (Mg) has been implicated in the regulation of sleep. We aimed to examine the longitudinal associations of Mg intake and Ca-to-Mg intake ratio (Ca:Mg) with sleep quality and duration. Methods The study sample consisted of 3,964 participants from the Coronary Artery Risk Development in Young Adults (CARDIA) study. Dietary and supplementary intake of Mg were obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…We found that magnesium levels are significantly higher in those who slept for 7 or more hours. Our results are in agreement with previous findings in animal models [ 45 ] and humans [ 46 , 47 , 48 ]. It is possible that magnesium may influence sleep duration via regulation of circadian rhythms [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…We found that magnesium levels are significantly higher in those who slept for 7 or more hours. Our results are in agreement with previous findings in animal models [ 45 ] and humans [ 46 , 47 , 48 ]. It is possible that magnesium may influence sleep duration via regulation of circadian rhythms [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…Further to the sleeping room, engaging in healthy lifestyle practices such as refraining from stimulants, eating or being on devices too close to bedtime, and unwinding from the day’s stresses with relaxation practices such as a warm bath or physical activity, need consideration [ 86 , 87 ]. From a nutritional standpoint, assessing dietary intake of macronutrients, especially tryptophan-containing sources of protein [ 87 ], along with micronutrients such as magnesium [ 88 ], vitamin D, and calcium, would be essential for ensuring a biochemical foundation that would foster healthy sleep [ 89 ]. Thus, melatonin would be utilized preferentially when the other changes have been implemented if there was an indication.…”
Section: Clinical Usesmentioning
confidence: 99%
“…A recent analysis using data from the National Health and Nutrition Examination Survey showed that participants with lower intakes of magnesium tended to have shorter sleep duration [ 70 ]. Similarly, in the Coronary Artery Risk Development in Young Adults study, those with the highest intakes of magnesium tended to report better sleep quality and showed lower odds of not achieving sufficient sleep duration of ≥7 h/night [ 71 ]. These observational data confirm a relationship between micronutrient cofactors of the Trp-melatonin pathway and sleep outcomes ( Figure 1 ).…”
Section: Micronutrients Common To Dairy and Involved In The Tryptopha...mentioning
confidence: 99%